2022
DOI: 10.1177/19485506221086182
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Speciesism: Age-Related Differences in the Moral View of Animals

Abstract: Humans care for the well-being of some animals (e.g., dogs) yet tacitly endorse the maltreatment of others (e.g., pigs). What treatment is deemed morally appropriate for an animal can depend on whether the animal is characterized as “food.” When such categorization of animals emerges and when a moral hierarchy of beings depending on their species membership (speciesism) develops is poorly understood. We investigate this development across samples of children (9–11 years old), young adults (18–21 years old), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
5
18
0
Order By: Relevance
“…This invites the possibility of each individual possessing (or at least expressing) a “net capacity” for moral concern: Increasing concern for some entities comes at the cost of concern for others. Our findings align with recent research showing that children and adults value human and nonhuman animal life differently (McGuire et al, 2022; Wilks et al, 2021) but that children’s preferences become more “adult-like” with age (Neldner et al, 2018). Importantly, we do not identify these human-centric shifts in children’s ratings for liking or knowing (e.g., liking and knowing remains relatively low for vulnerable entities at all ages, while liking for animals remains high across age groups).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This invites the possibility of each individual possessing (or at least expressing) a “net capacity” for moral concern: Increasing concern for some entities comes at the cost of concern for others. Our findings align with recent research showing that children and adults value human and nonhuman animal life differently (McGuire et al, 2022; Wilks et al, 2021) but that children’s preferences become more “adult-like” with age (Neldner et al, 2018). Importantly, we do not identify these human-centric shifts in children’s ratings for liking or knowing (e.g., liking and knowing remains relatively low for vulnerable entities at all ages, while liking for animals remains high across age groups).…”
Section: Discussionsupporting
confidence: 91%
“…However, certain moral considerations show distinct developmental shifts in childhood. As children age, they are more likely to prioritize vulnerable members of society, moving them into their inner circles of concern, and display a stronger tendency to prioritize humans over animals (McGuire et al, 2022; Neldner et al, 2018; Wilks et al, 2021). These shifts appear to occur alongside increasing capacities for perspective taking and empathic concern in middle childhood (between 7 and 11 years; Eisenberg et al, 1983, 1987; Helwig et al, 2001) and a growing awareness of inclusive social norms toward distal and vulnerable social groups (such as people with disabilities or chronic illnesses; Gasser et al, 2014; Nucci et al, 2017; Yoo & Smetana, 2019).…”
Section: The Moral Circlementioning
confidence: 99%
“…As such, animals can belong to different domains due to their perceived use by humans. Our findings also correlate with those of McGuire, Palmer, and Faber [ 57 ], who found that children (9–11 years old) will more often categorize farm animals as pets than food and find it less morally acceptable to eat meat and animal products compared to young adults and adults.…”
Section: Discussionsupporting
confidence: 89%
“…anthropogenic suffering; human and animal exploitation). These results are consistent with previous findings on the growing consumer awareness about the environmental impacts of the livestock industry (Hopwood et al, 2021;Krizanova et al, 2021;Sanchez-Sabate et al, 2019), as well as the impact that factory farms have on the animals who are used for human consumption (Hartmann and Siegrist, 2020;Mathur et al, 2021;McGuire et al, 2022;Rosenfeld, 2019). Sustainable and ethical consumption orientations have been identified as enablers of increased plant-based eating (Bryant, 2019;Hopwood et al, 2021;Graça et al, 2019).…”
Section: Levering Orientations Towards Sustainable Consumptionsupporting
confidence: 91%
“…, 2019), as well as the impact that factory farms have on the animals who are used for human consumption (Hartmann and Siegrist, 2020; Mathur et al. , 2021; McGuire et al. , 2022; Rosenfeld, 2019).…”
Section: Discussionmentioning
confidence: 99%